Using historical habitat loss to predict contemporary mammal extirpations in Neotropical forests - Bogoni, Juliano A.; Peres, Carlos A.; Navarro, Ana B.; Carvalho-Rocha, Vitor; Galetti, Mauro [UNESP] (Wiley, 2024)
Understanding which species will be extirpated in the aftermath of large-scale human disturbance is critical to mitigating biodiversity loss, particularly in hyperdiverse tropical biomes. Deforestation is the strongest driver of contemporary local extinctions in tropical forests but may occur at different tempos. The 2 most extensive tropical forest biomes in South America—the Atlantic Forest and the Amazon—have experienced historically divergent pathways of habitat loss and biodiversity decay, providing a unique case study to investigate rates of local species persistence on a single continent. We quantified medium- to large-bodied mammal species persistence across these biomes to elucidate how landscape configuration affects their persistence and associated ecological functions. We collected occurrence data for 617 assemblages of medium- to large-bodied mammal species (>1 kg) in the Atlantic Forest and the Amazon. Analyzing natural habitat cover based on satellite data (1985–2022), we employed descriptive statistics and generalized linear models (GLMs) to investigate ecospecies occurrence patterns in relation to habitat cover across the landscapes. The subregional erosion of Amazonian mammal assemblage diversity since the 1970s mirrors that observed since the colonial conquest of the Atlantic Forest, given that 52.8% of all Amazonian mammals are now on a similar trajectory. Four out of 5 large mammals in the Atlantic Forest were prone to extirpation, whereas 53% of Amazonian mammals were vulnerable to extirpation. Greater natural habitat cover increased the persistence likelihood of ecospecies in both biomes. These trends reflected a median local species loss 63.9% higher in the Atlantic Forest than in the Amazon, which appears to be moving toward a turning point of forest habitat loss and degradation. The contrasting trajectories of species persistence in the Amazon and Atlantic Forest domains underscore the importance of considering historical habitat loss pathways and regional biodiversity erosion in conservation strategies. By focusing on landscape configuration and identifying essential ecological functions associated with large vertebrate species, conservation planning and management practices can be better informed.
Keywords: Amazonia; Atlantic Forest; Bosque Atlántico; cacería; deforestación histórica; extinción local; habitat loss; historical deforestation; hunting; local extinction; pérdida de hábitat; 亚马逊流域; 历史上的森林砍伐; 大西洋森林; 局部灭绝; 栖息地丧失; 狩猎